«Inner Look» The photography as a tool of social transformation with women in the penitentiary of Algeciras - Conde de Vega, Alicia (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2018)
In this article, we reflect on photography as a tool for social transformation. Through the work carried out from 2009 to 2015 in the penitentiary of Algeciras with women prisoners through photography workshops under the title of «Inner Look», it has been proven that the creative process through the image allows the creation of a space of freedom, of encounter with themselves and with the group. Photography becomes a great tool to work on important aspects for personal and social development, reflect on their identity, to get better their self-concept and self-esteem, allowing them to recognize, accept, transform and meet before the camera, favoring decision-making, to be able to decide both individually and collectively what they want and how to show it. Thus, new communication processes are generated through the interaction that facilitates the photographic act, allowing in this way, to create more positive inter and interpersonal relationships by converting the time of sentence into an educational and socially useful time.